Vulnerability analysis on noise-injection based hardware attack on deep neural networks - Liu, Wenye (2020)
Despite superior accuracy on most vision recognition tasks, deep neural networks are susceptible to adversarial examples. Recent studies show that adding carefully crafted small perturbations on input layer can mislead a classifier into arbitrary categories. However, most adversarial attack algorithms only concentrate on the inputs of the model, effect of tampering internal nodes is seldom studied. Adversarial attack, if extends to deployed hardware system, can perturb or alter intermediate data during real time processing. To investigate the vulnerability implication of deep neural network hardware under potential adversarial attacks, we comprehensively evaluate 10 popular DNN models by injecting noise into each layer of these models. Our experimental results indicate that more accurate networks are more prone to disturbance of selective internal layers. For traditional convolutional network structures (AlexNet and VGG family), the last convolution layer is most assailable. For state-of-the-art architectures (Inception, ResNet and DenseNet families), as little as 0.1% or one element per channel of perturbations can subvert the original predictions, and over 65% of computational layers suffer from this vulnerability. Our findings reveal that optimization of accuracy, model size and computational efficiency can unconsciously sacrifice the robustness of deep learning system.